Exploring the Impact of Human Trafficking and Sexual Exploitation Toward Women Migrant Workers: A Case Study in Riau, Indonesia - Witarti, Denik; Faradina, Syarifah; Ridaryanthi, Melly; Puspita, Anggun (Social Sciences and Development Review, 2013)
The opportunity for working outside the homeland to pursue a better life is tempting, specially for those who are living unsettled in terms of economic context and with improper education. This situation has brought some issues pertaining to abuse of migrant workers, specially women. Human trafficking and commercial sexual exploitation toward them are considered as criminal violation of human rights. Reports from various sources pertaining to trauma, humiliation and fear of physical violence and psychological perception are alarming. Regarding the phenomenon described, this study is intended to give a comprehensive overview on the impact of this issue in Riau, Indonesia which is considered as one of the strategic points in Indonesia where deviation of migrant workers flow occurs. Data were analyzed by considering the practical implication of socio-culture, psychology, and the aspects of national security. Pull and push factors of the situation are revealed as the trigger of the desire for working abroad by considering the interaction among communities. Recommendations for holding counselling services to the victims to minimize their psychological distress, as well as improve their well-being, become part of the rehabilitation of victims. Trafficking as part of national security will be discussed critically as part of political aspects.